Inisiasi Live Streaming Minishow sebagai Inovasi Promosi Budaya Tari Tradisional dalam Membangun Reputasi Digital Sanggar Mugi Lestari: The Initiation of Live Streaming Minishow as an Innovation for Promoting Traditional Dance Culture and Strengthening Digital Reputation Sanggar Mugi Lestari - Romadhan, Mohammad Insan; Sudaryanto, Edy; Suwandha, Aisyah Indha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Digital transformation has significantly altered how society accesses and engages with cultural expressions, including traditional performing arts such as dance. Facing the challenges of globalization and a lack of generational regeneration, Sanggar Tari Mugi Lestari struggles to maintain its presence. This community service program initiates a live streaming mini-show to respond to those issues by integrating digital communication approaches and appropriate technologies. The implementation method is participatory, from technical needs assessment, content production training, and social media management to the regular execution of live streaming through Instagram and TikTok. Evaluation is conducted through pretests, posttests, and analysis of online content performance. The results show improved technical skills among the participants, activation of social media accounts, and live performances that successfully reached broader audiences. The digital content also serves as a cultural education medium by delivering contextual information such as the history of dances, meanings of movements, and local cultural values. This program enhances the community's ability to manage digital identity and opens opportunities for cross-sector collaboration and cultural monetization. Socially, live streaming encourages youth participation in cultural preservation by involving them as content creators. The initiative shows that live streaming is not merely a technological trend but an adaptive strategy for cultural sustainability that other art communities can replicate. These findings highlight the importance of policy support and educational interventions to expand digital transformation within local cultural ecosystems.